The Compositional Function of Phonostylistic Devices in Prose (with Reference to Literary Fairy Tales) - Olga Yuryevna Orlova (Известия Уральского федерального университета. Серия 2: Гуманитарные науки, 2017)
This article suggests that phonostylistic devices in fiction be considered from the semiological point of view. Sounds and sound clusters are traditionally seen as units without independent meaning. At the same time, being organised in a special way in the syntagmatics of the fictional text, they may acquire a specific “value” (as viewed by Saussure), which enables them to function in a given text or a part of the text as a sign. This article examines examples from literary fairy tales. Pragmatic purposes, typical of children’s literature, are realised among other things in the peculiar phonetic organisation of children’s literature genres including the literary fairy tale. Phonographical play, alliteration, spoonerism, the rhythmic organisation of prosaic narration, and other phonostylistic devices add a certain plane of content, typical of a specific text (description of a character, reference to a motif). Within the whole text, phonostylistic devices can contribute to a peculiar “marking”, which is in this article referred to as phonocomposition. The author puts forward a scheme which shows how attaching a functional meaning is added to a phonetic device within the text. The author also touches upon several methodological issues connected with phonostylistics.